Wpływ teorii makroekonomicznych na etyczną jakość praktyki finansowej - Wiśniewski, Jakub Bożydar (Annales. Etyka w Życiu Gospodarczym, 2019)
The aim of the present paper is to investigate the logical relationship between the prevalence of specific macroeconomic theories and the ethical quality of practices that take place in the financial markets. The main thesis presented herein is that viewing the financial markets through an appropriate economic framework is a crucial prerequisite of maintaining their ethical foundations and harnessing their ethical potential. Three competing macroeconomic visions – the “animal spirits” theory, the efficient market hypothesis, and the causal-realist market process approach – are assessed with respect to their logically deducible effects on the ethical thinking of financial operators. The main conclusion of the paper is that the causal-realist approach provides the most satisfactory account of the inherent conceptual nature of financial markets, thereby furnishing the best guidance for the development of appropriate professional virtues by their key members.